Hubungan Perilaku Penggunaan Air Terlindung Dan Jamban Layak Terhadap Angka Diare 2022 - Anhar, Khansa Hanifah; Martani, Natalia Sri; Teresa, Astrid; Widodo, Tri; Hanasia (Barigas: Jurnal Riset Mahasiswa, 2024)
In Indonesia, the prevalence of diarrhea was reported to be 1,516,438 cases among children. Children who experience diarrhea with unprotected water sources and use of improper latrines are stated to be higher than children with protected water sources and proper latrines. Therefore, this study was conducted to determine the relationship between environmental sanitation and the incidence of diarrhea in the Pahandut Health Center working area. This research method is non-experimental (Observative) with cross-sectional design. Sampling using purposive sampling technique with 100 respondents. Data collection using a questionnaire. Univariate analysis to show frequency distribution and bivariate analysis with chi square test with 95% confidence degree. The results of the bivariate analysis showed that the relationship between the behavior risk factors of using protected water and proper latrines had a p-value> 0.05, which means that there is no relationship between the use of protected water and the use of proper latrines.